Effect of Salvadora persica on resin-dentin bond stability - Manar M. Abu-Nawareg; Hanan K. Abouelseoud; Ahmed Z. Zidan (BMC, 2024)
Abstract Background The stability of resin-dentin interfaces is still highly questionable. The aim of this study was to evaluate the effect of Salvadora persica on resin-dentin bond durability. Materials and methods Extracted human third molars were used to provide mid-coronal dentin, which was treated with 20% Salvadora persica extract for 1 min after acid-etching. Microtensile bond strength and interfacial nanoleakage were evaluated after 24 h and 6 months. A three-point flexure test was used to measure the stiffness of completely demineralized dentin sticks before and after treatment with Salvadora persica extract. The hydroxyproline release test was also used to measure collagen degradation by endogenous dentin proteases. Statistical analysis was performed using two-way ANOVA followed by post hoc Bonferroni test and unpaired t-test. P-values < 0.05 were considered statistically significant. Results The use of Salvadora persica as an additional primer with etch-and-rinse adhesive did not affect the immediate bond strengths and nanoleakage (p > 0.05). After 6 months, the bond strength of the control group decreased (p = 0.007), and nanoleakage increased (p = 0.006), while Salvadora persica group showed no significant difference in bond strength and nanoleakage compared to their 24 h groups (p > 0.05). Salvadora persica increased dentin stiffness and decreased collagen degradation (p < 0.001) compared to their controls. Conclusion Salvadora persica extract pretreatment of acid-etched dentin preserved resin-dentin bonded interface for 6 months. Clinical significance Durability of resin-dentin bonded interfaces is still highly questionable. Endogenous dentinal matrix metalloproteinases play an important role in degradation of dentinal collagen within such interfaces. Salvadora persica may preserve resin-dentin interfaces for longer periods of time contributing to greater clinical success and longevity of resin composite restorations.